2019
DOI: 10.1097/md.0000000000014686
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and antimicrobial susceptibility profiles of culture-proven neonatal sepsis in a tertiary children's hospital, 2013 to 2017

Abstract: Neonatal sepsis (NS) remains a major cause of morbidity and mortality in neonates, but data on the etiology and antibiotic susceptibility patterns of pathogens are limited. The aim of this study was to analyze the clinical characteristics, risk factors, and the antibiotic susceptibility patterns of pathogenic microbes associated with NS at a tertiary children's hospital in Shanghai, China. Episodes of blood culture-proven sepsis in the neonatal intensive care unit (NICU) of Children's Hospital of Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 39 publications
8
35
4
Order By: Relevance
“…In some regions from developing countries, CoNS have been reported to play a less important role [22,23]. In China, Guo et al found that CoNS was the third common organism responsible for LOS in South China [24], while Li et al found that CoNS was the most common organism in Southeast China [25]. The results in our study are in line with Guo's study.…”
Section: Discussionsupporting
confidence: 90%
“…In some regions from developing countries, CoNS have been reported to play a less important role [22,23]. In China, Guo et al found that CoNS was the third common organism responsible for LOS in South China [24], while Li et al found that CoNS was the most common organism in Southeast China [25]. The results in our study are in line with Guo's study.…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, in 2016, the positive-cultured CVCs with staphylococci were primarily from the intensive care unit, and neonatal unit presented S. epidermidis predominantly. A study from China has displayed S. epidermidis was the principal organism and responsible for neonatal sepsis [33]. S. epidermidis is one of the common biofilm-producing bacteria affiliating colonization on indwelling or implanted foreign bodies [34].…”
Section: Discussionmentioning
confidence: 99%
“…[ 72 , 73 ] As for Gram-positive bacteria, although resistance to glycopeptide including vancomycin and linezolid seem to be rare in China, methicillin resistance was reported for 60% to 70% of Staphylococcus spp. [ 37 , 38 , 40 ]…”
Section: Empirical Treatment Of Neonatal Sepsismentioning
confidence: 99%